Upper cleft of the sternum. - Bastos, P; de Sousa, A R; Nunes, R; Gomes, M R (Acta Médica Portuguesa, 1990)
Superior sternal cleft is a rare congenital malformation that should be repaired during the first weeks of life, while the thorax is still complaint. We report the case of a two-week-old neonate with superior sternal cleft and describe the technique used to close the defect.